National breeding programs and variety release processes: A systematic review of how the interactions shape diversity and adoption of dryland legumes and cereals in Africa - Templer, Noel; Gatwiri, Judy; Nchanji, Eileen; Gichuru, Lilian; Puozaa, Doris; Ojiewo, Chris (SAGE Publications, 2025)
Dryland legumes and cereals are a good food source in Africa's drylands. However, their production is constrained by the limited availability of improved varieties and sustainable seed supply channels. The efficiency of breeding institutions and variety registration and release processes influence crop development and availability of a wide range of varieties in the market. The entire process influences the adoption of improved varieties, crop diversity, and the overall resilience of agricultural systems. Therefore, this article investigates how national breeding programs interact with registration and release processes for varieties to improve agricultural systems’ resilience in Africa. This study adopted the Preferred Reporting Items for Systematic Reviews and Meta-Analyses to identify and examine previous research. A total of 63 articles were reviewed. The study found that breeding efforts have focused on staple crops, neglecting dryland legumes and cereals. Among the significant challenges highlighted are limited resources and a weak regulatory framework. Additionally, poor communication between breeders and farmers and a lack of reliable data intensifies the challenges. Despite different stakeholders being involved in seed development and dissemination, they have poor coordination, which delays the introduction of new varieties. Furthermore, variety registration and release processes remain critical barriers to crop development. Hence, to promote agricultural productivity, improve seed accessibility, and enhance agricultural resilience in Africa, it is essential to streamline early-generation seed production and variety registration processes. It is also critical to enhance collaboration among all stakeholders in the seed production system and strengthen regulatory frameworks.